Observations of Energetic-particle Population Enhancements along Intermittent Structures near the Sun from the Parker Solar Probe - Riddhi Bandyopadhyay (2020)
© 2020. The American Astronomical Society. All rights reserved.. Observations at 1 au have confirmed that enhancements in measured energetic-particle (EP) fluxes are statistically associated with "rough" magnetic fields, i.e., fields with atypically large spatial derivatives or increments, as measured by the Partial Variance of Increments (PVI) method. One way to interpret this observation is as an association of the EPs with trapping or channeling within magnetic flux tubes, possibly near their boundaries. However, it remains unclear whether this association is a transport or local effect; i.e., the particles might have been energized at a distant location, perhaps by shocks or reconnection, or they might experience local energization or re-acceleration. The Parker Solar Probe (PSP), even in its first two orbits, offers a unique opportunity to study this statistical correlation closer to the corona. As a first step, we analyze the separate correlation properties of the EPs measured by the Integrated Science Investigation of the Sun (ISo˙IS) instruments during the first solar encounter. The distribution of time intervals between a specific type of event, i.e., the waiting time, can indicate the nature of the underlying process. We find that the ISo˙IS observations show a power-law distribution of waiting times, indicating a correlated (non-Poisson) distribution. Analysis of low-energy (∼15 - 200 keV/nuc) ISo˙IS data suggests that the results are consistent with the 1 au studies, although we find hints of some unexpected behavior. A more complete understanding of these statistical distributions will provide valuable insights into the origin and propagation of solar EPs, a picture that should become clear with future PSP orbits.